Unveiling the impact of the digital economy on future employment: a comparison study among selected Southeast Asian countries - Kunasegaran, Mageswari; Xing, Yidan; Kunjiapu, Shamuni (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explores the dynamics of the digital economy and the current progress of selected countries in Southeast Asia. Additionally, the Structural Change Theory adds valuable insights into the shifting employment patterns resulting from Industry Revolution 5.0. The digital economy is reshaping global markets, affecting multiple sectors, shaping economic growth as well as society. Through an exploration of the digitalization strategies and initiatives of the selected countries, this study seeks to offer insights into their distinctive approaches, challenges, and efforts in leveraging the potential of the digital economy. By analysis of these strategies, the study can contribute a deeper understanding of the importance of digital economy and impact towards society 5.0. Through a comprehensive review of relevant literature, policy documents, and current progress, the study highlights key factors driving digitalization in each country, including government policies, infrastructure development, investment climate, and digital skill levels. Moreover, the implication of the study will add values for employment patterns, innovation ecosystems, and inclusive growth strategies in China, Malaysia, and Indonesia. By synthesizing these findings, the study offers valuable insights for human resources practitioners, policymakers, business leaders, and stakeholders seeking to navigate the complexities of the digital economy and promote sustainable development in an increasingly digitalized world. Furthermore, the finding indicates that Southeast Asia countries are preparing for a shift in employment trends.